Ornamentation of the Antarala Ceiling - Temples of India Project Team (Jio Institute, 2024)
The antarala (vestibule or antechamber) is a rectangular passage that connects the mukhamandapa (front porch) and garbhagriha (sanctum sanctorum). The ceiling of the antarala is beautifully adorned with three square frames aligned in a row. Each of these square frames is decorated with a full-blown flower.